Controlled attenuation parameter and magnetic resonance spectroscopy-measured liver steatosis are discordant in obese HIV-infected adults. (24th September 2017) - Price, Jennifer C.; Dodge, Jennifer L.; Ma, Yifei; Scherzer, Rebecca; Korn, Natalie; Tillinghast, Kyle; Peters, Marion G.; Noworolski, Susan; Tien, Phyllis C.
Abstract : Objective: Hepatic steatosis is common in HIV-infected individuals. Magnetic resonance spectroscopy (MRS) is the preferred noninvasive method for hepatic steatosis measurement but is expensive. Controlled attenuation parameter (CAP) also assesses hepatic steatosis and is conveniently performed concomitantly with transient elastography. We aimed to assess the accuracy of CAP in the setting of HIV infection. Design: Cross-sectional study. Methods: CAP and MRS were performed in 82 study participants (39 HIV monoinfected; seven hepatitis C virus (HCV) monoinfected; 21 HIV/HCV coinfected; 15 with neither infection). We used concordance correlation coefficients to compare log-transformed and standardized CAP and MRS values and linear regression to examine factors associated with CAP and MRS-measured hepatic steatosis (MRS-HS). The accuracy of CAP to detect at least mild hepatic steatosis, defined as MRS-liver fat fraction more than 0.05, and the factors associated with discordance between CAP and MRS were evaluated. Results: Overall, CAP-measured hepatic steatosis and MRS-HS correlated moderately well ( r c  = 0.63; P  < 0.001), and correlation was strongest in the HIV-monoinfected group ( r c  = 0.67; P  < 0.001). Body composition factors (higher BMI, waist circumference, visceral and abdominal subcutaneous adipose tissue) and insulin resistance were significantly associated with both greater CAP-measured hepatic steatosis and MRS-HS. Using a validated CAP cut-off of at least 238 dB/m, sensitivity and specificity for at least mild hepatic steatosis were 84% and 75% in the entire cohort; 89% and 80% in the HIV-monoinfected group. Participants with higher body composition parameters were more likely to be misclassified as having hepatic steatosis by CAP. Conclusion: Our findings suggest CAP is an acceptable noninvasive surrogate for hepatic steatosis in HIV-infected individuals but may overestimate hepatic steatosis prevalence, especially in individuals with high BMI. Evaluation of factors that improve CAP accuracy and determination of optimal cut-offs are warranted.